Formation of aluminium hydride (AlH3) via the decomposition of organoaluminium and hydrogen storage properties - Wang, L.; Rawal, A.; Quadir, Md Zakaria; Aguey-Zinsou, K. (Elsevier Ltd, 2017)
© 2017 Hydrogen Energy Publications LLC. Aluminium hydride (AlH3) is a promising hydrogen storage material due to its competitive hydrogen storage density and moderate decomposition temperature. However, there is no convenient way to prepare/regenerate AlH3from (spent) Al by direct hydrogenation. Herein, we report on a novel approach to generate AlH3from the decomposition of triethylaluminium (Et3Al) under mild hydrogen pressures (10 MPa) with the use of surfactants. With tetraoctylammonium bromide (TOAB), the synthesis led to the formation of nanosized AlH3with the known a phase, and these nanoparticles released hydrogen from 40 °C instead of the 125 °C observed with bulk a-AlH3. However, when tetrabutylammonium bromide (TBAB) was used instead of TOAB, larger nanoparticles believed to be related to the formation of ß-AlH3were obtained, and these decomposed through a single exothermic process. Despite the possibility to form a-AlH3under low conditions of temperature (180 °C) and pressure (10 MPa), TOAB stabilised AlH3was found to be irreversible when subjected to hydrogen cycling at 150 °C and 7 MPa hydrogen pressure.